The Principal's Strategy for Managing Conflicts Due to the Stress of Female Teachers as a Result of the Implementation of Full Day School - Hertining Dyah Listiningrum; Tobari Tobari; Nila Kesumawati (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This study aimed at determining the principal's strategy to manage work stress conflicts in female teachers as the impact of implementing Full Day School. This research was conducted using qualitative methods with the type of phenomenological research. The research sites were SMAN 1 Talang Kelapa and SMAN 1 Betung Banyuasin Regency. The data in this study were in the form of observations, documentation, and interviews. Checking the validity of the data with source triangulation and method triangulation. Data analysis using the Spradley model The results in this study indicate that the principal conducts three strategies to manage work stress conflicts in female teachers as the impact of implementing Full Day School so that it does not interfere with teacher performance, student comfort, and does not hinder the achievement of school goals. The strategies adopted by the principal are 1) identifying the forms of work stress for female teachers, 2) identifying conflicts that arise as the effects of work stress for female teachers, and 3) resolving conflicts through personal approaches, official services, and religious approaches.